Otherization in Muhsin Hamid’s The Reluctant Fundamentalist and Ali Eteraz’s Native Believer (Langues & Cultures)
Ultimate objective of this research paper is to deeply explore the notion of otherization in a diverse and multinational society like America. In my study I have opted for two important and well-read novels, which are Muhsin Hamid‘s The Reluctant Fundamentalist and Ali Eteraz‘s Native Believer . The two literary works focalize on two multinational protagonists of Pakistani and Afghani origin . 09/11 attacks in America have been a turning point in America and in the world especially the Western world that has blamed Islam and Muslim for the tragedy of the 09/11 attacks which have triggered enormous reactions on the part of politicians and literary writers who have made the events a raw material to show how American Muslims have been victimized for being Muslims. The monolithic view of the West has made of American Muslim outsiders and intruders despite their American nationality. The characters endeavour to forge a space in their society but they have been marginalized and otherized in a society where freedom should be guaranteed for every one regardless of his origin and the color of his skin. In addition to that the study will focus on how the main characters struggle to make their voice heard and their identity asserted, which are a big challenge for Muslim Americans. It is important to highlight that the mass media have played crucial role in mobilizing the public against Islam as religion that breeds terrorism and terror in the world.